Health needs of people with diabetes mellitus for disease management: a scoping review - Florência Gamileira Nascimento; Amelina de Brito Belchior; Raquel Rodrigues da Costa Brilhante; Marília Araripe Ferreira; Carmem Carmem Meyve Pereira Gomes; Maria Luiza Pereira Costa; Sherida Karanini Paz de Oliveira (Universidade Federal do Ceará, 2024)
Objective: to map the health needs of people with diabetes mellitus for disease management. Methods: scoping review according to the JBI guided instead by the guiding question: what are the health needs of people with diabetes for managing their health condition? Health databases and portals were analyzed using the descriptors Diabetes mellitus, Health service needs and demands, Needs assessment, Disease management, and the keyword Health needs. Results: the analysis consisted of 26 studies, the majority published in 2019, carried out in Europe, with people with type 2 diabetes and in a hospital setting. Health needs were listed in four thematic categories. Conclusion: people with diabetes mellitus have educational, behavioral, supportive, and emotional health needs, and these needs are interconnected, impacting disease management and quality of life. Contributions to practice: with our findings, it is possible to guide research in the area, guiding researchers to design educational interventions that can meet the needs presented. In addition, it will also guide professionals in their clinical practice to reflect on the care they provide, helping them to make decisions to direct the planning and execution of care.